2021
DOI: 10.3390/cimb43030126
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Endogenous Putative TSH Binding Protein in Orbit

Abstract: Thyroid stimulating antibodies (TSAB) cause Graves’ disease and contribute to Graves’ Orbitopathy (GO) pathogenesis. We hypothesise that the presence of TSH binding proteins (truncated TSHR variants (TSHRv)) and/or nonclassical ligands such as thyrostimulin (α2β5) might provide a mechanism to protect against or exacerbate GO. We analysed primary human orbital preadipocyte-fibroblasts (OF) from GO patients and people free of GO (non-GO). Transcript (QPCR) and protein (western blot) expression levels of TSHRv we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The findings of Woeller et al (54) also demonstrate that TSHR signalling in GO-OFs stimulates proliferation indirectly through induction of miR-146a and miR-155, reducing the expression of ZNRF3 and PTEN that normally block cell proliferation. The latest interesting study by Draman MS et al suggests a variant in TSHR that might explain the antigenic role of this receptor in OF even prior to adipogenesis (55). In conclusion, TSHR plays a specific role in GO pathogenesis and has become a therapeutic target.…”
Section: Autoantigens In the Pathogenesis Of Go Tshrmentioning
confidence: 81%
See 1 more Smart Citation
“…The findings of Woeller et al (54) also demonstrate that TSHR signalling in GO-OFs stimulates proliferation indirectly through induction of miR-146a and miR-155, reducing the expression of ZNRF3 and PTEN that normally block cell proliferation. The latest interesting study by Draman MS et al suggests a variant in TSHR that might explain the antigenic role of this receptor in OF even prior to adipogenesis (55). In conclusion, TSHR plays a specific role in GO pathogenesis and has become a therapeutic target.…”
Section: Autoantigens In the Pathogenesis Of Go Tshrmentioning
confidence: 81%
“…The latest interesting study by Draman MS et al. suggests a variant in TSHR that might explain the antigenic role of this receptor in OF even prior to adipogenesis ( 55 ). In conclusion, TSHR plays a specific role in GO pathogenesis and has become a therapeutic target.…”
Section: Autoantigens In the Pathogenesis Of Gomentioning
confidence: 99%
“…Furthermore, induced murine models of GD and GO are more effective when immunizing with the A subunit than with the complete TSHR ( 74 , 75 ). We have reported that the 1.3 variant is expressed as a protein and can affect TSHR activation ( 76 ). Thus, these variants could have impact on the pathogenesis of GO by inducing further production of TSAB or protect against GO by ‘neutralizing’ TSAB, respectively.…”
Section: Tshr Variantsmentioning
confidence: 99%
“…The thyrotropin receptor (TSHR) is a G protein coupled receptor found in thyroid follicular epithelial cells, adipocytes, osteocytes and cardiomyocytes [14]. It has been reported that TSHR was upregulated along with intraorbital preadipocytes of GO patients differentiated into mature adipocytes [15][16][17]. The PI3K/AKT pathway is a known TSHR signal transduction pathway in Graves' disease [18].…”
Section: Introductionmentioning
confidence: 99%